Do Governance Mechanisms Shape Cash Holdings? Evidence from Female Directors and Board Structures in Indonesia - Siti Muntahanah; Heru Cahyo; Muhamad Firmansyah; Rizka Fauziyatun Nisa (Fundamental and Applied Management Journal, 2026)
This study aims to analyze the influence of corporate governance mechanisms on cash holding policies in Indonesian companies. The corporate governance variables used in this study include female directors, board of directors, independent commissioners, board of commissioners, and audit committee. This study uses a quantitative approach with panel data regression analysis on companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The results show that female directors, board of directors, and independent commissioners have a positive and significant effect on cash holding policies, while board of commissioners and audit committee policies do not. These findings indicate that corporate governance mechanisms play a significant role in enhancing corporate prudence in managing liquidity. This study contributes to the corporate governance literature and provides practical implications for companies in strengthening governance structures to improve financial stability.